2021
DOI: 10.1093/jamia/ocab009
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between electronic health records and provider burnout: A systematic review

Abstract: Objective Stress and burnout due to electronic health record (EHR) technology has become a focus for burnout intervention. The aim of this study is to systematically review the relationship between EHR use and provider burnout. Materials and Methods A systematic literature search was performed on PubMed, EMBASE, PsychInfo, ACM Digital Library in accordance with the PRISMA (Preferred Reporting Items for Systematic Reviews and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 58 publications
2
59
0
Order By: Relevance
“…Nurses still commonly use practice systems that are lacking basic usability (eg, contributing to alert fatigue, reinforcing disruptive workflow processes) or generate added documentation burdens because of poor configuration and optimization. 54 There is huge variation globally in access to, integration of, and sustainability of digital technology. 55 -57 Solutions vary and are context specific.…”
Section: Embrace Digital Practicementioning
confidence: 99%
See 1 more Smart Citation
“…Nurses still commonly use practice systems that are lacking basic usability (eg, contributing to alert fatigue, reinforcing disruptive workflow processes) or generate added documentation burdens because of poor configuration and optimization. 54 There is huge variation globally in access to, integration of, and sustainability of digital technology. 55 -57 Solutions vary and are context specific.…”
Section: Embrace Digital Practicementioning
confidence: 99%
“…Too often, technology to support nursing is poorly configured, resourced, or not upgraded to respond to practice and societal trends. Nurses still commonly use practice systems that are lacking basic usability (eg, contributing to alert fatigue, reinforcing disruptive workflow processes) or generate added documentation burdens because of poor configuration and optimization 54…”
Section: Embrace Digital Practicementioning
confidence: 99%
“…The result is a clunky and often frustrating experience for clinicians, associated with increasing time in the electronic chart, confusion, preventable errors, and clinician burnout. 8 9 10 11 12 13 14 15 16 17 18 19 20 21 Clinicians must cope with EHRs that are difficult to navigate and contain large amounts of duplicated, scattered, conflicting, and erroneous information. 15 Further, many EHRs are poorly matched to clinicians' operational models for care delivery.…”
Section: Background and Significancementioning
confidence: 99%
“…Correct Answer: Option b is the correct answer. As we have learned in recent studies, 12 clinicians are spending more and more time in front of a computer to be able to complete the required work to care for patients. Time–motion studies have shown that clinicians are spending approximately 50% of their time in front of the EHR or on other tasks at a desk and approximately 27% on direct patient care.…”
Section: Multiple Choice Questionsmentioning
confidence: 99%
“…which accounts for a significant number of working hours of medical professionals [2]. In turn, this is one of the factors contributing to their low job satisfaction and burn out [3,4,5,6,7]. A study conducted in the context of the British National Health Service suggests that 20% of the work of general practitioners is devoted to administrative tasks [8].…”
Section: Introductionmentioning
confidence: 99%